KINERJA KEUANGAN SEBAGAI MEDIASI PENGARUH GCG DAN CSR TERHADAP NILAI PERUSAHAAN PADA SEKTOR INDUSTRI BARANG KONSUMSI - Suharningsih, Ririn; Hariyanti, Widi; Harjito, Yunus (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
This study aims to examine the effect of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on firm value by mediating financial performance. Company value is proxied using the Tobin's Q ratio. The GCG variable is measured by five indicators, namely the Board, Audit Committee, Independent Commissioner, Managerial Ownership, and Institutional Ownership. CSR variable is measured using indicators issued by Global Reporting Initiatives version G4 with a total of 91 items. Meanwhile, the Financial Performance variable is proxied by Return On Assets. The sample in this study was obtained by 33 companies in the consumer goods industry sector with a research period of 3 years (2017-2019). Data analysis using Structural Equation Modeling with Smart PLS 3.3.3 program. The results showed that GCG proved to have a significant effect on Financial Performance and Firm Value. However, CSR is not proven to have an effect on Financial Performance and Firm Value. Meanwhile, Financial Performance is expected to mediate the relationship between GCG and CSR to Company Value, but the results will not be proven.